APPROACHES TO SELECTING REMOTE ENVIRONMENTS FOR AUTOMATED IT-PRODUCT TESTING - Mary Sergeevna Krivozjateva (Science and Innovation Center Publishing House, 2020)
In a competitive environment, testing software and end-to-end systems is becoming one of the most popular uses for virtual internet platforms. With the digitalization of the economy, not only is an increasing number of entrepreneurs moving into electronic business, but trends in the IT industry are also changing the vector of their action towards remote development and testing through the Internet and mobile applications.